Os Sete Ricercari de Domenico Gabrielli e suas aplicações no ensino do violoncelo - Dutton, Leah Elizabeth (2017)
This work endeavors to analyze the seven Ricercari for solo cello written by Domenico Gabrielli, as well as develop a strategy for their incorporation into the standard cello repertoire. These pieces, composed in 1689 in Bologna, Italy, represent the first examples of the solo genre for the instrument. This change in paradigm, as well as the modifications made to the instrument itself, were of great significance to the evolution of the cello into a solo instrument. Our present examination of these works determines their relevance in the study of modern and Baroque techniques, and displays the increasing importance of the cello to composers in the seventeenth century. These seven Ricercari are some of the most virtuosic and technically demanding pieces written for the cello up until this point, as the instrument typically performed the more relaxed role of doubling the figured bass line in ensembles. Although they were originally composed as technical studies, there is evidence that these Ricercari were written as etudes for Gabrielli’s students. Within its pages exist frequent changes of position, chords, double stops, dotted rhythms, rapid scales, and virtuosic ornamentation. This dissertation is based on ample bibliographical research, with theoretic references to the authors Dimitry Markevitch, Robin Stowell, Marc Vanscheeuwijck, Stephen Bonta, and Gregory Barnett. Besides providing historical contextualization, this work possesses a strong pedagogical stimulus that seeks to demonstrate the importance of this repertoire, previously unexamined, to the study of the cello. Our objectives are to examine the history that created Gabrielli’s Ricercari, as well as formulate a pedagogical plan for the teaching of this repertoire to modern cellists. It will discuss this work’s applicability as preparatory material for the approach of advanced cello repertoire, through a thorough analysis of period-appropriate scordatura, bowings, shifting, and fingerings. These considerations come to fruition within the annex of this dissertation, as our own performance edition of the seven Ricercari is presented. This edition contains all of Domenico Gabrielli’s Ricercari, and provides suggested bowings, fingerings, and expression marks, based on Baroque period practices and modern techniques, to facilitate the addition of this piece of music into the classroom.